Recommendations for the Management of Incidental Pancreatic Findings in Adults by the Canadian Association of Radiologists Incidental Findings Working Group. Issue 2 (May 2022) - Fung, Christopher I.; Bigam, David L.; Wong, Clarence K. W.; Hurrell, Casey; Bird, Jeffery R.; Brahm, Gary L.; Kirkpatrick, Iain D. C.
The Canadian Association of Radiologists Incidental Findings Working Group consists of both academic subspecialty and general radiologists and is tasked with adapting and expanding upon the American College of Radiology incidental findings white papers to more closely apply to Canadian practice patterns, particularly more comprehensively dealing with the role of ultrasound and pursuing more cost-effective approaches to the workup of incidental findings without compromising patient care. Presented here are the 2021 Canadian guidelines for the management of pancreatic incidental findings. Topics covered include anatomic variants, fatty atrophy, pancreatic calcifications, ductal ectasia, and management of incidental pancreatic cysts.